Perilaku Pembelian Hedonis Generasi Z: Promosi Pemasaran, Kelompok Acuan, dan Konsep Diri - Ramadhan, Andre Fachrun; Simanjuntak, Megawati (Jurnal Ilmu Keluarga dan Konsumen, 2018)
Sometimes consumers can not understand their needs and desaires that can cause hedonic buying behavior.The aim of this research was to analyze the effects of marketing promotion, reference group and self-concept onhedonic buying behavior in generation Z. The study was conducted by online survey. Data analysis useddescriptive analysis, factor analysis, structural equation modeling (SEM) and independent sample t-test. SEManalysis in this study used statistical software of Smart PLS 3 and Analisis of Moment Structures (AMOS) 22,0.Two hundred and twenty two collage students have been selected by stratified proportionate random samplingand divided into science group and social group. The result showed that self-concept had significant effect on thehedonic buying in the science group. The marketing promotion and reference group have significant effects onhedonic buying behavior both in science group and social groups. The research also showed a significantdifference in the variable promotion, reference group, self-concept and hedonic buying behavior between sciencegroup and social group.